REPRODUCTIVE STATUS OF WOMEN OF ADVANCED MATERNAL AGE (World Science, 2021)
The purpose of the study: to study, evaluate and comparative analysis of the causes of reproductive health disorders, to identify socio-hygienic characteristics of women of late reproductive age with infertility.Materials and methods. The study was performed continuously, included 1297 women who underwent infertility treatment by in vitro fertilization from 2019 to 2021. at the state IVF center. Of these, the basic group - 530 women of late reproductive age (35-49 years), average age - 37.01 + 2.02 years. The comparison group included 767 women with infertility aged 20- 35 years, average age - 30 + 2.79 years. The medical status of patients was assessed according to a comprehensive objective examination. Social status - based on the results of the survey.Results. We have found significant differences in the causes of infertility in women of advanced maternal age (from 35 to 49 years) in comparison with infertile women age below 35 years. The predominant causes of infertility in the basic group are the combined factor (42%), multiple female factors (20%) and reduced ovarian reserve (17%). A significantly smaller percentage of women presented the absolute tubal factor (6%) or no gynecological pathology but isolated male factor infertility (9%). The comparative analysis of the social status of the women from the basic and the reference group has found no fundamental differences.Conclusions. Significant differences in the causes of infertility in women of advanced maternal age, the frequency of labors, the assessment of the social situation of infertile women of advanced maternal age are the basis for the development of ways of optimization of the specialized medical assistance for infertile couples and the improvement of the efficiency of treatment.